Risk of bleeding and predictors of hemorrhagic transformation in patients with stroke after thrombolysis - Daniela Barella; Karina de Oliveira Azzolin; Michelle Dornelles Santarém; Ruy de Almeida Barcellos; Luísa Brehm Santana (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To analyze the prediction of hemorrhagic transformation in patients with ischemic stroke undergoing thrombolytic therapy and its association with the nursing diagnosis “Risk of bleeding”. Method: Retrospective cohort study in patients with post-thrombolysis ischemic stroke from a hospital in Rio Grande do Sul from January 2019 to December 2021. The patient data were extrected from electronic medical records. After processing, univariable and multivariable analysis was conducted using Poisson regression with robust variance. Results: 249 patients were analyzed, 43 (17.4%) had hemorrhagic transformation, hospitalization time was 8 (5-12.5) days and 25 (10%) died. The predictors of hemorrhagic transformation were: increased age, pre-thrombolysis National Institute of Health Stroke Scale score and use of oxygen therapy via nasal goggles and Hudson mask. The nursing diagnosis “Risk of bleeding” was not associated with hemorrhagic transformation. Conclusion: The predictors found can improve the nursing diagnosis “Risk of bleeding”, but there was no correlation observed between this and the occurrence of hemorrhagic transformation.